مصطلح "ليس بالقائم": دراسة تطبيقية لمن قال الإمام البخاري فيهم، أو في مروياتهم، أو في الطريق إليهم "ليس بالقائم" - الحارثي، محمد بن سالم بن عبدالله (جامعة الأمير سطام بن عبدالعزيز, 2023)
تناول هذا البحث دراسة مصطلح: "ليس بالقائم"، عند المحدثين، وبيان مرادهم منه، مع دراسة تطبيقية على الرواة الذين قال الإمام البخاري فيهم أو في مروياتهم، أو في الطريق إليهم: "ليس بالقائم"، وعددهم ثلاثة عشر راوياً، ويهدف البحث إلى: بيان معنى مصطلح: "ليس بالقائم"، من خلال تطبيقات أئمة النقد، وإطلاقاتهم على الرواة والمرويات، واعتمدت في البحث على المنهج الاستقرائي والاستنباطي، ومن أهم نتائج البحث: أن معنى: "ليس بالقائم": أي: ليس بثابت ومستقيم، استقامة حديث أهل الضبط والإتقان، وهو: وصف لإسناد الحديث الذي لا يُعتبر به، إما لضعف أحد رواته، أو جهالته، أو اضطرابه، أو تفرده، أو عدم موافقة راويه للثقات في مروياتهم، لقلتها، ومن توصيات البحث: دراسة المصطلحات الأخرى التي يطلقها الأئمة على المرويات، وبيان مدلولها عندهم من خلال السبر لهذه الأقوال، ودراستها، ودراسة هذا المصطلح عند الأئمة الآخرين كأبي أحمد الحاكم، وأبي الفتح الأزدي، وابن عبد البر، وغيرهم. The present study dealt with the term "unsteady" according to the Hadith scholars, explaining what they meant by it. It offered an applied investigation of the works of thirteen Hadith narrators described by al Imam al-Bukhari as “unsteady.” The study aimed at illuminating the meaning of the term "unsteady," through the applications of critics, and their applications to both Hadith narrators and Hadith narrations. The current study adopted inductive and deductive methodological approaches in data collection and analyses. The most significant findings of the study include that the meaning of "unsteady" is not fixed and straight when compared with the credibility of the thorough narrators of Hadith. It is mainly a description of the validation of Hadiths. Being “unsteady” is usually attributed to narrators' weakness, lack of knowledge, slip-up, eccentricity, or disagreement with trustworthy Hadith narrators in their narrations for purposes of paucity. The study proposed a number of recommendations, and these include the call for studying other terms used by Hadith Imams when referring to narrations and clarifying the meaning of those terms by examining their work. It also called for investigating the use of the term under investigation by other Hadith Imams, e.g. Abu Ahmad al-Hakim, Abu Al-Fath al-Azdi, Ibn Abdul-Barr, and others.
Keywords: البخاري، محمد بن إسماعيل، ت. 256 هـ. -- العلماء المسلمون -- الأحاديث النبوية -- علم الجرح والتعديل -- رواة الأحاديث